A systematic review of microbiome composition in osteoarthritis subjects - Bonato, A.; Zenobi-Wong, M.; Barreto, G.; Huang, Z. (Osteoarthritis and cartilage, 2022)
Osteoarthritis (OA) started to be associated to shifted microbiota composition recently. This systematic review aims to elucidate if there is a common microbiota composition linked with OA between different studies. We screened PubMed, Scopus, Web of Science and Cochrane databases up to July 26th 2021 to identify original studies in which microbiome was assessed from OA individuals, both in human and laboratory animals’ studies. Bacteria associated with OA were summarized to find common patterns between the studies. We identified 37 original studies where the microbiota composition was assessed in OA subjects. We identified some bacteria (Clostridium, Streptococcus, Bacteroides and Firmicutes) that were reported to be upregulated in OA subjects, whereas Lactobacillus and Bifidobacterium longum were associated with improved OA outcomes. The heterogeneity of sampling and analysis methods, different taxonomical levels reported and the lack of healthy controls in several studies made it difficult to compare the studies and reach conclusions about a potential causal link. The current study demonstrated that some bacteria were identified as regulators of OA. Future works following standardized methodologies with more proper controls are needed to elucidate our understanding of the role of the microbiota in OA pathogenesis and progress towards new treatments.